ANALISIS SITASI SKRIPSI SEBAGAI SUMBER REFERENSI SKRIPSI MAHASISWA PENDIDIKAN A GAMA ISLAM (PAI) FAKULTAS TARBIYAH UNIVERSITAS ISLAM NEGERI (UIN) SULTAN SYARIF KASIM (SUSKA) RIAU TAHUN 2013 - Suhaila, Suhaila; Amelia, Vita (Universitas Lancang Kuning, 2015)
The purpose of this research is to analyze the citation of Holy Qur 'an on thesis of students of religious education, Tarbiyah Faculty, Islamic Universities of (UIN) Riau, citation frequency, surah and verses of the most widely cited and determine whether there is any indication of plagiarism in the same paragraph citation. Method used is statistic descriptive. The results show that, there are 43 citations in Qur'an and from 5316 citations listed in 39 bibliography thesis of 247 thesis with percentage 0,80%, (classified as very low criteria). The most cited verses and surah are surah Al-Baqarah verse 129, An-Nahl verse 125, At-Tahrim verse 6, Luqman verse and Al Alaq verse 1-5. There are conditions of plagiarism on citation explanation surah At-Tahrim verse 6. The plagiarism is found on class 66 to class 65 theses, the evidence showed from it approval sheet date and thesis using the ideas of others without mentioning the obvious sources.